The role of endolysosomal progranulin and TMEM106B in neurodegenerative diseases - Hideyuki Takahashi; Stephen M. Strittmatter (Molecular Neurodegeneration)
Abstract Although different neurodegenerative diseases are defined by distinct pathological proteins, they share many common features including protein aggregation. Despite this commonality, most current therapeutic approaches in the field, such as anti-aggregate antibodies, are focused on individual diseases or single neuropathologies with only limited success. The endolysosomal proteins progranulin and TMEM106B were both initially associated with frontotemporal lobar degeneration but have subsequently also been linked to other neurodegenerative diseases. Thus, these proteins are predicted to participate in common pathogenic pathways shared across various neurodegenerative diseases. Importantly, recent discoveries of TMEM106B amyloid fibrils in varied neurodegenerative diseases and glycosphingolipid regulation by progranulin and TMEM106B further support their central roles in cross-disease neurodegenerative mechanisms. This review summarizes recent advances in progranulin and TMEM106B function within the endolysosomal system and neurodegenerative diseases. It describes preclinical models and therapeutic approaches for progranulin- and TMEM106B-associated diseases. We also discuss future direction leading to novel alternative therapies targeting shared mechanisms in neurodegenerative diseases.